FORMULASI MINYAK GOSOK DARI BIJI PALA (Myristica fragrans) DAN UJI ANTIBAKTERI TARHADAP BAKTERI Staphylococcus aureus - Jayanti Djarami; Aulia Debby Pelu; Sardila Bugis (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
Nutmeg is known as a spice plant that has economic value and multipurpose because every part of the plant can be used in various industries. Compounds contained in nutmeg seeds include essential oils, a-pinene, b-pinene, limonene, myristicin, safrole, and methyl eugenol. Nutmeg plant nutritious as antidiarrheal, antidiabetic, antimicrobial. The purpose of this study was to make a formulation of rubbing oil and to determine the bacteriostatic activity of nutmeg seed oil on staphylococcus aureus bacteria. This study used three formulations, namely the provision of distilled water as a negative control, chloramphenicol as a positive control. The method used in this research is the well method. Bacteria that were incubated for 24 hours in the fastest concentration inhibition research were at 50% concentration because of bacterial growth which showed that the higher the concentration, the higher the inhibitory power and at 20% concentration the results were resistant, because the amount of solvent used was higher. low and can not inhibit the growth of microorganisms.